Pathological social withdrawal syndrome and the paradox of new technologies - Markovic, Milos; Kato, Takahiro A. (Engrami, 2024)
The concept of the "Fourth Industrial Revolution" highlights its transformative impact on industries and society through technologies like artificial intelligence and robotics, which blur the lines between the physical, digital, and biological realms. This extends into the psychological realm, prompting questions about our ability to adapt to rapid technological changes. "Hikikomori" (Japanese) or pathological social withdrawal, a condition, characterized by an extreme form of social isolation, was first recognized in Japan. While initially seen as culturally specific, hikikomori has become a global issue. Early developmental factors such as family dynamics and later environmental factors and stressors contribute to this condition, while the role of technology, including increased internet use, is not completely clear. We explore here the relationship between technological advances and pathological social withdrawal and the hypothetical dual role of these advances- promoting isolation on one hand, and offering potential therapeutic benefits on the other.
Keywords: hikikomori; pathological social withdrwal; robots; technological advances; treatment